Analisis Konflik Batin dalam Film Penyalin Cahaya Sutradara Wregas Bhanuteja - Elmustian, Elmustian; Charlina, Charlina; Melani, Endah (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is a type of qualitative descriptive research. The purpose of this research is to describe Kurt Lewin's inner conflict of approaching, moving away, approaching and moving away. Based on the results of the research